(untitled) - Hannagan, Tim (London, UK, 1998)
The book has been fully updated and includes the latest ideas on management development. The chapter on information systems management introduces a section on communications and the Internet, and includes a discussion of the World Wide Web. Recent legislation on equal opportunities is discussed in the of human resources management, which also includes up-to-date material on sexual harassment in the workplace and ageism.
Keywords: Management